Stress and failure analysis of the connecting rod of diesel engine. (March 2019) - Witek, Lucjan; Zelek, Paweł
Abstract: In this study the failure and stress analysis of the connecting rod of turbocharged diesel engine was performed. Visual examination of the fracture showed that beach marks, typical for the fatigue failure were observed. Additional observations of the crack initiation area indicated that the crack origins were not covered by products of corrosion or the material defects. In order to explain the reasons of connecting rod damage, an advanced stress analysis using the finite element method (FEM) was utilized. In order to solve the problem the geometrical models of connecting rod, piston and adjacent components were created. Next the complex loads resulting from both the pressure of gas in cylinder and the inertial forces were defined. The contact between all touching surfaces of considered components was defined. The results of nonlinear static analysis showed that during work of engine with the maximum power the high stress zones were located in crack origins. Obtained results indicated that the bolt tightening torque has a significant influence on maximum value of stress at crack origin. Based on results of performed investigations it was concluded that the main reason of the connecting rod's failure was a high stress levels in zones near the bolt hole caused by high pretension of bolts. The crack initiation process could also be accelerated by small radius of fillet on surface near the bolt hole. In consequence the notch effect caused additional stress concentration in the critical zone of the connecting rod. In last part of the work the recommendations for increase of the fatigue life of connecting rod were formulated. Highlights: In a diesel engine the fatigue failure of the connecting rod was occurred. The crack origins were not covered by corrosion products and material defects. Maximum stress zones were located near the bolt hole and overlap the crack origins. Main reason of fatigue fracture of the connecting rod was to high torque of bolts. Crack initiation was accelerated by small fillet radius and stress concentration.